Petangan Jawa: Installing traditional values in names - Ajar Pradika Ananta Tur; Aris Munandar; Daru Winarti (NOTION: Journal of Linguistics, Literature, and Culture, 2023)
This research contributes to investigate a cultural continuity, particularly naming practice, in a homogenous Javanese community installing Petangan Jawa (Javanese Calculations). However, common Javanese slowly ignore it. This study employs a descriptive qualitative approach with fieldwork to investigate the intention behind the name. Therefore, two varieties of Petangan Jawa, namely, a calculation based on calendar properties and a calculation based on Javanese script values, are still consistently used. In addition, this study paves the way for future research on the causes of the gradual abandonment of Petangan Jawa among common Javanese and how the perspective of religious beliefs about Petangan Jawa is used to predict the future.